Perioperative complications of orthotopic neobladder after radical cystectomy for carcinoma of urinary bladder: A Retrospective Study - Nepal, Umesh; Gautam, Nischal; Gharti, Binod Babu; Pokhrel, Gyan Prasad; Pokhrel, Bharat Mani; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2024)
Background: The gold standard treatment for muscle-invasive bladder cancer is radical cystectomy (RC) with urinary diversion. Urinary diversion is performed in either as continent or incontinent forms. Orthotopic neobladder has the benefits of continent reservoir with voiding from the urethra. The mortality and morbidity rates ranged from 0 to 9.0% and 30 to 70%, respectively in various reports. For surgical outcome assessment, Clavien-Dindo classification is widely accepted for classification of complications of most of the surgical procedures. This study will be helpful to identify the potential complications and possibly minimize the morbidity and mortality of this surgery in the future. Materials and Methods: Data of 20 consecutively enrolled patients who underwent radical cystectomy and orthotopic neobladder form January 2023 to July 2024 at Urology unit of B.P. Koirala Memorial Cancer Hospital were taken for study from hospital medical records. The various demographic data and perioperative parameters were recorded. The early complications were defined as the complications during the period of hospitalization and up to 30 days of surgery, they were enlisted and then classified according to Clavein-Dindo Classification and the continence was reviewed at 1 month of surgery after catheter removal and after 3 months of surgery. Data was entered in SPSS 27 software and analyzed. Results: Complications were seen in 18 (90%) patients out of which 1 (5%) patients had Grade I complication, 12 (60%) patients had Grade II, 3 (15%) patients had grade IVA and 2(10%) had died. 5 (25%) patients developed high grade(≥ Grade III) complications. Mortality rate was 5%. Conclusion: Radical cystectomy with any forms of diversion is associated with high rate of morbidity and mortality. In order to identify and minimize the complications of this surgery in future, Clavein-Dindo classification is the standardized way of reporting the complications.